2016
DOI: 10.1007/s11060-016-2113-1
|View full text |Cite
|
Sign up to set email alerts
|

Executive dysfunction is associated with poorer health-related quality of life in pediatric brain tumor survivors

Abstract: Background Children with brain tumor (BT) are at risk for a number of physical and cognitive problems that may lower their health-related quality of life (HRQoL). Executive functioning (EF) and intellectual ability are hypothesized to associate with HRQoL and deficits in these areas may be amenable to interventions. Objective To investigate intellectual function, EF, and HRQoL following conformal radiation therapy (CRT) for pediatric BT. Method Forty-five BT survivors (age 12.68±2.56) treated with CRT part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 27 publications
3
48
1
1
Order By: Relevance
“…Eight papers included appropriate self‐report data and four papers included parent‐proxy data. Three studies included comparison data for Leukemia survivors, four included data of acute lymphoblastic leukemia survivors, and one paper included comparison data for solid tumor survivors …”
Section: Resultsmentioning
confidence: 99%
“…Eight papers included appropriate self‐report data and four papers included parent‐proxy data. Three studies included comparison data for Leukemia survivors, four included data of acute lymphoblastic leukemia survivors, and one paper included comparison data for solid tumor survivors …”
Section: Resultsmentioning
confidence: 99%
“…Survivors with a stroke history were less likely to be married and to progress to postsecondary education, and were more likely to be unemployed or unable to work and more likely to fail to achieve independent living compared with their counterparts without a stroke history. Previous studies have shown that survivors of childhood cancer who demonstrated lower neurocognitive outcomes also demonstrated worse HRQOL, and were more likely to be economically dependent and to demonstrate lower earning ability, and stroke appears to contribute to these risks . These previously established risks combined with the newly demonstrated overall increased negative impact of stroke and stroke recurrence on HRQOL and long‐term morbidity in survivors of pediatric cancer identify a high‐risk population.…”
Section: Discussionmentioning
confidence: 98%
“…Netson and colleagues identified associations between parental reports of both child executive function and HRQOL after radiotherapy for a brain tumor; however, associations were less compelling between parent-reported executive function and child-reported HRQOL. 29 In survivors of osteosarcoma, Edelmann and colleagues observed that variability in sustained attention and slower processing speeds were associated with poorer general health, while variability in sustained attention alone was associated with worse physical function. 25 Our results suggest that objectively measured processing speed and survivor-reported executive function are associated with worse HRQOL in NHL survivors.…”
Section: Discussionmentioning
confidence: 99%